Softlifting Intention of Students in Academia: A Normative Model - Rahim, Md. Mahbubur; Abd. Rahman, Mohd. Noah; H. Seyal, Afzaal (Malaysian Journal of Computer Science, 2000)
Softlifting refers to the practice of sharing software with friends, co-workers, and others. It is a form of software piracy that is widely practised in academia. Past studies on software piracy were primarily undertaken in the western world. These studies had focused on the ‘self-reported software piracy behaviour’. Students may not reveal their actual piracy behaviour due to social bias. This study was conducted in Brunei Darussalam to examine the softlifting intention of students. A normative model was developed, which was validated using 432 responses. Three interesting findings have emerged. Firstly, the factors affecting students’ softlifting intention vary depending on the nature of task. Secondly, students’ software piracy attitude, gender and PC ownership, were found to be significantly related with their softlifting intention. Thirdly, students’ software piracy attitude had more impact on their softlifting intention. The implications of these findings are discussed.